Respuesta :
Answer:
-13
Step-by-step explanation:
See steps below:
- 2(3x+6)=3(x-9) ⇒ distribution
- 6x + 12 = 3x - 27 ⇒ grouping like terms
- 6x - 3x = -27 - 12 ⇒ simplifying
- 3x = -39
- x= -39/3
- x = -13 ⇒ answer
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Hi my lil bunny!
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
[tex]\boxed{-13}[/tex]
Let's solve your equation step-by-step.
[tex]2(3x+6)=3(x-9)[/tex]
Step 1: Simplify both sides of the equation.
[tex]2(3x+6)=3(x-9)[/tex]
[tex](2) (3x) + (2) (6) = (3)(^{x}) + (3) (-9)[/tex] (Distribute)
[tex]6x + 12 = 3x + -27[/tex]
[tex]6x + 12 = 3x -27[/tex]
Step 2: Subtract 3x from both sides.
[tex]6x + 12 - 3x = 3x - 27 - 3x\\3x + 12 = -27[/tex]
Step 3: Subtract 12 from both sides.
[tex]3x + 12 - 12 = -27 - 12\\3x = -39[/tex]
Step 4: Divide both sides by 3.
[tex]\frac{3x}{3} = \frac{-39}{3}\\x = -13[/tex]
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Have a great day/night!
❀*May*❀